Hellenic Language and Thought in Pre-Conquest England - Eleni Ponirakis (Anglica. An International Journal of English Studies)
Bede, reflecting on the success of the Canterbury school set up by Theodore of Tarsus remarked: “some of their students still alive today are as proficient in Latin and Greek as in their native tongue” [trans. Colgrave and Mynors 1969, 335]. By the time we get to the court of Alfred two hundred years later, there had been a famous decline in learning from which Greek, as a language, had not yet recovered. However, there remained a strong interest in Greek as a sacred language in liturgies, prayers and magical charms, and later in hermeneutic poetry. Theodore’s influence was not limited to Greek Language, he also brought knowledge of Maximus the Confessor and Pseudo-Dionysius. The influence of Greek mystical theology would find fuller expression in the translations associated with the court of King Alfred via contact with the Carolingian court, but the seeds for this reception in England may already have been sown. This paper will outline the evidence for the use of Greek language in a variety of contexts, including a charm for the staunching of blood, and it will examine the extent of the influence of Greek patristic thinking in Old English texts including both clerical prose and secular poetry.